Extracorporeal shockwave enhanced regeneration of fibrocartilage in a delayed tendon‐bone insertion repair model. Issue 4 (23rd December 2013) - Chow, Dick Ho Kiu; Suen, Pui Kit; Huang, Le; Cheung, Wing‐Hoi; Leung, Kwok‐Sui; Ng, Chun; Shi, San Qiang; Wong, Margaret Wan Nar; Qin, Ling
ABSTRACT Fibrous tissue is often formed in delayed healing of tendon bone insertion (TBI) instead of fibrocartilage. Extracorporeal shockwave (ESW) provides mechanical cues and upregulates expression of fibrocartilage‐related makers and cytokines. We hypothesized that ESW would accelerate fibrocartilage regeneration at the healing interface in a delayed TBI healing model. Partial patellectomy with shielding at the TBI interface was performed on 32 female New Zealand White Rabbits for establishing this delayed TBI healing model. The rabbits were separated into the control and ESW group for evaluations at postoperative week 8 and 12. Shielding was removed at week 4 and a single ESW treatment was applied at week 6. Fibrocartilage regeneration was evaluated histomorphologically and immunohistochemically. Vickers hardness of the TBI matrix was measured by micro‐indentation. ESW group showed higher fibrocartilage area, thickness, and proteoglycan deposition than the control in week 8 and 12. ESW increased expression of SOX9 and collagen II significantly in week 8 and 12, respectively. ESW group showed a gradual transition of hardness from bone to fibrocartilage to tendon, and had a higher Vickers hardness than the control group at week 12. In conclusion, ESW enhanced fibrocartilage regeneration at the healing interface in a delayed TBI healing model. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:507–514, 2014.